Biometric Analysis of Melanoma Cells Due to Various Metastasis Origin - N. V. Palkina; A. V. Komina; M. B. Aksenenko; T. G. Ruksha (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
Objective: biometric analysis of melanoma cells derived from different types of primary or secondary tumors could be necessary for better understanding tumor heterogeneity as that phenomenon would affect significantly the anti-cancer therapy efficacy. Materials and Methods. A comparative analysis of melanoma cells that reflect different stages of tumor progression was accomplished with following parameters tested: intensity of apoptosis, proliferation/metabolic activity, the ratio of the cell cycle phases distribution, chromosomal constitution analysis, invasion, and migration capacity. Results. It was found that melanoma cells derived from visceral metastases characterized by a high proliferative/metabolic potential, migratory ability, and mitotic potential. Melanoma cells which represent earlier stages of carcinogenesis have higher invasive activity and percentage of polyploidy cells, indicating high mutational potential. Both cell lines have no differences in the expression of apoptosis. Conclusion. Melanoma cells derived from metastasis demonstrate various abilities for growth, migration, and invasion depending on metastasis origin. In that context, isolation of pathological cells and tissues, both native and fixed, followed by their individual testing for each patient will have a high demand for both fundamental and clinical medicine for more adequate therapy choice.